Information System Design and Implementation Web-Based New Student Admissions (PPDB) Using the Waterfall Method (Study Early Childhood Kindergarten Dharma Women's Case of Kebur Village) - Dina Precilia; Apriansyah; Karnadi; Dedi Haryanto (Universitas Islam Kuantan Singingi, 2025)
Information technology continues to grow in response to societal needs, including the education sector which increasingly depends on digital systems. One of the essential processes in school administration is the Admission of New Students (PPDB), which serves as the first stage of school services to the public. At PAUD TK Dharma Wanita Kebur Village, the PPDB process is still conducted conventionally, requiring parents or guardians to come directly to the school, resulting in inefficiencies in time, effort, and data management. This study develops a web-based PPDB information system as a solution to improve the accuracy, speed, and convenience of the admission process. The Waterfall method is used in system development, consisting of sequential stages including requirements analysis, design, implementation, testing, and maintenance. Data collection was conducted through literature studies and analysis of existing registration procedures. The designed system includes features such as user login, online registration, prospective student data input, validation, and automated registration processing. The final result is a web-based PPDB system that is expected to make the student admission process more efficient, structured, and accessible for both schools and prospective students, while supporting better data management in educational institutions.